2020
DOI: 10.1002/adma.202004853
|View full text |Cite
|
Sign up to set email alerts
|

Activating Macrophage‐Mediated Cancer Immunotherapy by Genetically Edited Nanoparticles

Abstract: traditional treatment modalities in the clinic. [1,2] Macrophages are a significant constituent of innate immune system and have an indispensable impact in activating body's first-line defense against infection and cancer. [3] Effectively activating macrophage-mediated immunity holds great potential in cancer immunotherapy. [4] However, cancer cells are masters of immunomodulation and express "don't eat me" signal CD47 on the cellular surface, protecting them from the phagocytosis via binding to signal regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(139 citation statements)
references
References 49 publications
0
122
0
Order By: Relevance
“…For example, Rao et al . reported that the magnetic nanoparticles can be used to promote the repolarization of the M2‐like TAMs as well as the systemic circulation and tumor accumulation of the loaded drugs 397 . Notably, there are still some challenges for the effective targeting of TAMs with nanoparticles and their application in the clinic.…”
Section: Pharmacological Modulation Of Tamsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rao et al . reported that the magnetic nanoparticles can be used to promote the repolarization of the M2‐like TAMs as well as the systemic circulation and tumor accumulation of the loaded drugs 397 . Notably, there are still some challenges for the effective targeting of TAMs with nanoparticles and their application in the clinic.…”
Section: Pharmacological Modulation Of Tamsmentioning
confidence: 99%
“…For example, Rao et al reported that the magnetic nanoparticles can be used to promote the repolarization of the M2-like TAMs as well as the systemic circulation and tumor accumulation of the loaded drugs. 397 Notably, there are still some challenges for the effective targeting of TAMs with nanoparticles and their application in the clinic. The major one can be attributed to the undesirable clearance of nanoparticles by the mononuclear phagocyte system (macrophages) in clearance organs (liver, lung, or spleen) upon their intra-venous injection.…”
Section: Nanoparticle or Exosomal-targeted Deliverymentioning
confidence: 99%
“…[ 12 ] For instance, various nanoparticles have been functionalized with high affinity to specific molecular targets, providing alternative options to the biological ligands, such as antibodies and proteins. [ 32,33 ] These engineered nanoparticles have been employed to detain and neutralize bacterial toxins, animal venoms, and inflammatory cytokines. [ 56,57,90 ] Other high‐affinity molecules, such as aptamers, have also been conjugated onto various biomaterials as potential alternatives to free antibodies for cytokine neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are heterogeneous immune cells that link innate and adaptive immune responses, and are able to initiate rapid protection against pathogens. [31][32][33][34] In response to infection, monocyte-derived macrophages are recruited from blood circulation to the site of infection in order to orchestrate prompt immune response. [34,35] Equipped with pattern recognition receptors (PRRs), macrophages can identify pathogen-associated molecular patterns (PAMPs) and conduct phagocytosis and phagolysosome-mediated digestion of pathogens, therefore facilitate proinflammatory response.…”
Section: Macrophages In Covid-19 Cytokine Stormmentioning
confidence: 99%
“…TAMs, as a kind of myeloid immune cell, have been reported to the important prognostic significances in human malignancies [ 16 ]. Current studies found that an increased infiltration in the TME is associated with a worse prognosis for lung and breast cancer patients [ 23 , 24 ]. Besides lung and breast cancer, increased accumulation of TAMs in gastric cancers and multiple myeloma is also associated with a poor prognosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%